(untitled) (Journal of Organizational Psychology, 2021)
This paper examines workplace bullying, the repeated, harmful mistreatment of an employee by other employee(s). Extensive research on workplace bullying has generated overwhelming evidence to support a long list of qualitative conclusions that challenge most traditional assumptions. Institutional responses to workplace bullying, which tend to be guided by these traditional assumptions, typically intensify the problem and often trigger the loss of high-quality employees. The research identifies a set of policies and procedures that offers greater likelihood of success. Key recommendations include establishing a workplace culture of mutual respect, holding leaders accountable for promoting that culture, and educating the workforce.